On history, archive, and theory a review of Nick Deocampo’s Eiga: Cinema in the Philippines during World War II - Sonido, Louise Jashil (Plaridel, 2017)
Access online through this link: https://www.plarideljournal.org/article/history-archive-theory-review-nick-deocampos-eiga-cinema-philippines-world-war-ii-2016